The Antidiabetic Effect of Grape Skin Extracts of Selected Indigenous Croatian White Grapevine Varieties - Vesna Rastija; Mato Drenjančević; Toni Kujundžić; Luka Zmaić; Maja Karnaš (Foods)
Grape skin is an excellent bioactive compound source with numerous beneficial health effects. This study aimed to determine and compare the antidiabetic potential of the grape skin of indigenous Croatian white grapevine varieties. The grape skin extracts (GSEs) were assessed for total polyphenols, antioxidant activity, and inhibition potential against α-amylase and α-glucosidase, enzymes responsible for carbohydrate metabolism. GSE of variety “Svetokriška belina” has the highest total phenols (TP) content (1404.87 mg of gallic acid equivalent), the highest antioxidant capacity against DPPH (544.82 mg ascorbic acid equivalent), and the highest inhibitory activity against α-amylase (99.60%). α-glucosidase was best inhibited by the variety “Kozjak” (93.53%), followed by a significantly lower inhibition by the GSE of “Svetokriška belina” (89.64%). The principal component analysis (PCA) revealed the relationship among the grape varieties by their inhibition potential, where the first PC explained 71.34% of the variation. Indigenous Croatian white grapevine varieties have great potential for developing new natural supplements to prevent and treat diabetes.